A Systematic Review of the Data-Driven Public Policy Making in Indonesia - Pebriani Wahyu, Fitri; Alia, Siti; Susanti, Elisa; Hanif Abdillah, Fauzan; Febrianti, Ranti (Indonesian Association for Public Administration (IAPA), 2024)
Decision-making for public policy formulation in Indonesia has undergone significant changes from year to year, one of which is due to the effects of digital transformation. Big data is a part of digital transformation that has a direct correlation with public policy formulation in Indonesia. This research aims to identify the utilization of big data in decision-making for public policy formulation in Indonesia. The matters discussed in this research include the decision-making process in formulating public policy in Indonesia using big data analysis, as well as the effectiveness, efficiency, and openness of public policies resulting from data-driven public policy in Indonesia. This research uses the Systematic Literature Review (SLR) method by collecting various related research documents into a database using the PRISMA (Preferred Reported Items for Systematic Reviews and Meta-Analysis) research procedure. The utilization of big data in decision-making for public policy formulation in Indonesia has proven that the policies formulated are more effective and efficient because they utilize the data available in big data analysis.